Partnership practices and their impact on value creation – reflections from lean management - Jylha, Tuuli; Junnila, Seppo (International Journal of Strategic Property Management, 2014)
The trend of outsourcing operational property management services by the property owners has had a prominent role in the Finnish real estate sector. At the same time, value creation has been scattered across many players such as the owner, the property manager and several service providers. This paper aims to analyse the value creation practices and mechanisms between two partners, a real estate owner and its property management company, in order to assess the current value creation. The assessment is based on a lean partnering framework presented by Lamming (1993). The customers are office tenants in the Helsinki business district. The case findings showed that the expected customer value was challenging to deliver, because waste activities disrupted the value creation. The partners had also adapted some of the value creation practices differently, which caused turbulence in value creation. In addition, the partners had missed the power of doing improvements jointly, but prefer to use bidding to establish value creation. However, through lean thinking the organisations found a much-needed new approach to develop their partnership. The principles of lean management made the problem clearer and enabled the organisations to start dealing with the relevant challenges. First Publish Online: 21 Mar 2014